1978
DOI: 10.1073/pnas.75.7.3517
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for existence of a yearly clock in surgically and self-blinded chipmunks.

Abstract: By use of simplified technique and constant environmental conditions, I have demonstrated the existence in the chipmunk of a yearly clock. In a blinded chipmunk the clock manifested itself by remarkably consistent changes in running activity, food and water intake, and body weight over 61/2 yr. Studies on freshly trapped chipmunks kept in the same laboratory environment but with alternating light and darkness (12 hr each), showed that, when their eyes were covered for much of the light period, they reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Captive chipmunks exposed to natural envir-Onmental temperatures entered torpor in winter and Spring but did not estivate in summer (Wang and Hudson 1971). Richter (1978) presented data supporting the contention that the activity-inactivity phases of the Eastern Chipmunk are controlled by a yearly clock which is set by, but not dependent on, photoperiod. The winter inactivity phase is clearly shown by his data, but no other inactivity period is evident.…”
supporting
confidence: 52%
“…Captive chipmunks exposed to natural envir-Onmental temperatures entered torpor in winter and Spring but did not estivate in summer (Wang and Hudson 1971). Richter (1978) presented data supporting the contention that the activity-inactivity phases of the Eastern Chipmunk are controlled by a yearly clock which is set by, but not dependent on, photoperiod. The winter inactivity phase is clearly shown by his data, but no other inactivity period is evident.…”
supporting
confidence: 52%
“…Circannual rhythms have been found to persist for several cycles in both birds and mammals, suggesting that a circannual clock can function throughout the life of an individual (Pengelley and Asmundson, 1969;Pengelley and Asmundson, 1974;Richter, 1978;Gwinner, 1986). The most compelling evidence for circannual rhythms comes from experiments in which captive birds kept on constant and 'neutral' photoperiods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…photoperiod and weight cycles have been plagued ~~~k (1955) noted that body weights in C. un-by two uncertainties: (1) wild-caught animals may dulatus increased as photoperiod decreased and have been entrained to the natural photoperiod suggested that short days might act as a stimulus for prior to their exposure to artificial ~h o t o~e~~o~~ hibernation. Richter (1978) and Brenner and Lyle and (2) weight changes may be caused by shifts in water content in the gut and (or) accumulation of 'Present address: Department of Zoology and Entomology, body fat. It was, therefore, our purpose to deter- cumulation of body fat in C .…”
Section: Introductionmentioning
confidence: 99%